2018
DOI: 10.1371/journal.pone.0209583
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-like weak inducer of apoptosis induces inflammation in Graves’ orbital fibroblasts

Abstract: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK), along with its receptor fibroblast growth factor-inducible (Fn)14, is associated with various biological activities including inflammation. However, its role in the pathogenesis of Graves’ orbitopathy (GO) is unknown. In this study, we investigated the mechanism by which TWEAK regulates inflammatory signaling in orbital fibroblasts from GO patients. We found that TWEAK and tumor necrosis factor-α (TNFA) mRNA levels were upregulated in GO as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
3
4
0
Order By: Relevance
“…Blocking the FN14-TWEAK-pathway resulted in a significant reduction of IL-6 concentration in the CNV microenvironment with a tendency to also decrease IL-33, CXCL2 and CCL5, although the differences were not significant. These results are in accordance with studies on human astrocytes (Saas et al, 2000) and orbital fibroblasts (Lee et al, 2018) as well as murine synovial (Kamata et al, 2006) and mesangial cells (Campbell et al, 2006), which have shown FN14-TWEAK activation to induce IL-6, CXCL2 and CCL5 secretion, respectively. These results may indicate that FN14 influences CNV development, at least in part, through modulation of IL-6, although this does not exclude other soluble factors to be regulated by the treatment with the FN14 decoy receptor.…”
Section: Discussionsupporting
confidence: 92%
“…Blocking the FN14-TWEAK-pathway resulted in a significant reduction of IL-6 concentration in the CNV microenvironment with a tendency to also decrease IL-33, CXCL2 and CCL5, although the differences were not significant. These results are in accordance with studies on human astrocytes (Saas et al, 2000) and orbital fibroblasts (Lee et al, 2018) as well as murine synovial (Kamata et al, 2006) and mesangial cells (Campbell et al, 2006), which have shown FN14-TWEAK activation to induce IL-6, CXCL2 and CCL5 secretion, respectively. These results may indicate that FN14 influences CNV development, at least in part, through modulation of IL-6, although this does not exclude other soluble factors to be regulated by the treatment with the FN14 decoy receptor.…”
Section: Discussionsupporting
confidence: 92%
“…Blocking the FN14-TWEAK-pathway resulted in a significant reduction of IL-6 concentration in the CNV microenvironment with a tendency to also decrease IL-33, CXCL2 and CCL5, although the differences were not significant. These results are in accordance with studies on human astrocytes (Saas et al, 2000) and orbital fibroblasts (Lee et al, 2018) as well as murine synovial (Kamata et al, 2006) and mesangial cells (Campbell et al, 2006), which have shown FN14-TWEAK activation to induce IL-6, CXCL2 and CCL5 secretion, respectively. These results may indicate that FN14 influences CNV development, at least in part, through modulation of IL-6, although this does not exclude other soluble factors to be regulated by the treatment with the FN14 decoy receptor.…”
Section: Discussionsupporting
confidence: 92%
“…And these factors promote proliferation and differentiation of epithelial cells and endothelial cells [105], then might induce cancers. Lee et al found TNF-like weak inducer induced inflammation with real-time polymerase chain reaction (RT-PCR), western blotting, and enzyme-linked immunosorbent assay (ELISA) [106]. Khodabandehlon et al found the existence of human papillomavirus was related to tumor progress and the increase of inflammatory cytokines (IL-6, IL-17, IL-1, NF-κB, TNF-α, and TGF-β) with ELISA and RT-PCR [107].…”
Section: Proinflammatory Factors and Inflammatory Factors In Chronic mentioning
confidence: 99%